Poetry in Speech Orality and Homeric Discourse - Bakker, Egbert J. (Myth and Poetics, 1997)
Applying linguistic theory to the study of Homeric style, Egbert J. Bakker offers a highly innovative approach to oral poetry, particularly the poetry of Homer. By situating formulas and other features of oral style within the wider contexts of spoken language and communication, he moves the study of oral poetry beyond the landmark work of Milman Parry and Albert Lord. One of the book's central features, related to the research of the linguist Wallace Chafe, is Bakker's conception of spoken discourse as a sequence of short speech units reflecting the flow of speech through the consciousness of the speaker. Bakker shows that such short speech units are present in Homeric poetry, with significant consequences for Homeric metrics and poetics. Considering Homeric discourse as a speech process rather than as the finished product associated with written discourse, Bakker's book offers a new perspective on Homer as well as on other archaic Greek texts. Here Homeric discourse appears as speech in its own right, and is freed, Bakker suggests, from the bias of modern writing style which too easily views Homeric discourse as archaic, implicitly taking the style of classical period texts as the norm. Bakker's perspective reaches beyond syntax and stylistics into the very heart of Homeric-and, ultimately, oral-poetics, altering the status of key features such as meter and formula, rethinking their relevance to the performance of Homeric poetry, and leading to surprising insights into the relation between "speech" and "text" in the encounter of the Homeric tradition with writing.